Altered properties of mitochondrial ATP-synthase in patients with a T-->G mutation in the ATPase 6 (subunit a) gene at position 8993 of mtDNA - Houstĕk, J; Klement, P; Hermanská, J; Houstková, H; Hansíková, H; Van den Bogert, C; Zeman, J (Biochimica et biophysica acta, 1995)
A family is described with a T-->G mutation at position 8993 of mtDNA. This mutation is located in the ATPase 6 gene of mtDNA which encodes subunit a of the ATP-synthase complex (FlFo-ATPase). Clinically, the patients showed severe infantile lactate acidosis and encephalomyopathy in a form that was different from the classical Leigh syndrome. In 3 affected boys, ranging in age from 3 months to 8 years, the mutation was found in 95-99% of the mtDNA population. The clinical symptoms correlated with the mtDNA heteroplasmy and in the healthy mother 50% of the mtDNA was mutated. The rate of mitochondrial ATP production by cultured skin fibroblasts containing 99% of mutated mtDNA was about 2-fold lower than that in normal fibroblasts. Native electrophoresis of the mitochondrial enzyme complexes revealed instability of the FlFo-ATPase in all the tissues of the patient that were investigated (heart, muscle, kidney, liver). Only a small portion of the ATP-synthase complex was present in the complete, intact form (620 kDa). Incomplete forms of the enzyme were present as subcomplexes with approx. molecular weights of 460, 390 and 150 kDa, respectively, which differed in the content of F1 and Fo subunits. Immunochemical analysis of the subunits of the FlFo-ATPase further revealed a markedly decreased content of the Fo subunit b in mitochondria from muscle and heart, and an increased content of the Fo subunit c in muscle mitochondria, respectively. These results indicate that in this family the T-->G point mutation at position 8993 in the mitochondrial ATPase 6 gene is accompanied by structural instability and altered assembly of the enzyme complex, that are both most likely due to changes in the properties of subunit a of the membrane sector part of the ATP-synthase.
Keywords: acidóza laktátová; mitochondriální DNA; DNA, Mitochondrial; Mitochondria; Male; Pedigree; mutace; rodokmen; Acidosis, Lactic; srdeční mitochondrie; Proton-Translocating ATPases; Infant; Child; dítě; mužské pohlaví; Mitochondria, Heart; lidé; Humans; kojenec; Mutation; protonové ATPasy; mitochondrie